Digital proficiency and the learning of brazilian nursing institutions' history in the pandemic. - Maia, Natália Maria Freitas e Silva; Araújo, Agostinho Antônio Cruz; Santos, Ana Maria Ribeiro dos; Santos, Fernanda Batista Oliveira; Aperibense, Pacita Geovana Gama de Sousa; Andrade, Elaine Maria Leite Rangel (Acta Paulista de Enfermagem, 2023)
Objective: To characterize the digital proficiency of nurse students about the history of Brazilian nursing class institutions. Methods: Exploratory-descriptive, cross-sectional study carried out in the Nursing bachelor's degree from three campuses of a federal public higher education institution in northeastern Brazil. We applied, from November 2020 to May, a questionnaire via Google Forms to nurse students regularly registered in the second and third periods of the course. We carried out statistical, descriptive, and inferential analyses. Results: 56 nurse students participated in the study, of which 55.64% were from campus 1; 53.6% attended the third semester, 83.9% were female; average age of 20.55 (+3.32) years old; 55.4 were brown; 94.6% with no employment relationship; 73.2% living with their parents; 92.9% with a monthly family income of three minimum wages. We considered the average degree of basic digital proficiency low. Regarding the digital technologies in teaching and the learning about the class institutions' history, 62.5% believed that it contributed to the learning process, besides the classroom space and it eased the access to content, and 78.6% considered it important to develop a critical-reflexive sense and the awareness about the participation of these institutions. They found it fundamental to know the creation history, contributions, struggles, challenges, and first directors of the Brazilian Nursing Association, besides the creation of the Nursing Federal and Regional Councils and the respective attributions. Conclusion: The teaching-learning process mediated by digital technologies needs to consider the digital competencies and students' interest in remote teaching about the nursing class institutions' history.